DEVELOPMENT OF A PCR PROTOCOL FOR THE DETECTION OF HUMAN ENTEROVIRUSES BASED ON THE ANALYSIS OF THE 5’-NTR REGION AND IT’S USE IN MOLECULAR EPIDEMIOLOGY - Kamalova , D.K.; Kuybagarov , M.A.; Abeev , A.B.; Shvedyuk , V.B.; Balykbaev , K.O.; Kiyanbekova , L.S.; Aushakhmetova , Z.T.; Shevtsov , A.B. (Eurasian Journal of Applied Biotechnology, 2017)
Enterovirus infections are widespread throughout the world. The clinical manifestation of enterovirus infection can lead to serious and fatal complications. Express PCR diagnosis and genotyping allows controlling the epidemiological situation and predicting the severity of the infection. In Kazakhstan, there are no locally produced PCR test kits. In addition there is no regular monitoring of circulating genotypes of enteroviruses. This study was aimed to develop a PCR protocol for the enterovirus detection based on the amplification of the 5’ untranslated region (5’ NTR) and genotyping by sequencing of enteroviruses circulating in Kazakhstan in 2016 - 2017. In this study 74 cDNA samples were used. The results obtained with developed protocol were well correlated (97.3%) with the results of the commercial PCR testing kit. The advantage of the developed protocol is genotyping of enteroviruses by sequencing of the amplified DNA fragment. Fifty nine samples were genotyped, of which 54.7% belong to enterovirus B, 35.9% are classified as enterovirus A and 1.56% are classified as enterovirus C. Ninety-three percent of meningitis-associated genotypes were identified as enterovirus B, and clustered with E-9, E-18, CV-B5 and E-30. Samples of DNA that isolated from patients with enterovirus infection were clustered with the CV-A6 genotype.